Processing mediated enhancement of ferroelectric and electrocaloric properties in Ba(Ti0.8Zr0.2)O3–(Ba0.7Ca0.3)TiO3 lead-free piezoelectrics. Issue 13 (October 2021) - Ramana, E. Venkata; Ferreira, N.M.; Mahajan, A.; Tobaldi, D.M.; Bdikin, I.; Rožič, B.; Kutnjak, Z.; Valente, M.A.
Abstract: High-performance Ba(Ti0.8 Zr0.2 )O3 –(Ba0.7 Ca0.3 )TiO3 (BCZT) fiber crystals were grown using laser-heated pedestal growth (LHPG) for a systematic investigation of processing effects on structure and physical properties. By changing the growth rate (200−5 mm/h), fiber crystals with varying stoichiometry were realized: controlled composition, Ba0.872 Ca0.128 Ti0.925 Zr0.075 O3-δ, for the optimized crystal (5 mm/h), relative to the ceramic sample (SS) synthesized by the ceramic method. SS and optimized fibers exhibited larger energy storage densities of 700 and 868 mJ/cm 3, respectively. Electrocaloric (EC) measurements by direct and indirect methods yielded ΔT of 1.3 K & 0.95 K and EC responsivity (ΔT/ΔE) of 0.3 and 0.43 K mm/kV for SS and 5 mm/h respectively, at 30 kV/cm, at least two-folds higher compared to 200 mm/h fiber. The EC responsivity of our samples is comparable to that of Pb(Mg, Nb)O3 crystals. These results demonstrate that BCZT has potential application as EC elements when the composition is controlled by fine-tuning of growth parameters.